Beyond Soft Power: A Critical Review of Inequality, Authenticity, and Sustainability in Food Diplomacy - Nazir, Novizar; Putri, Annisyia Zarina; Putri, Aisyah Shakira; Hariry, Amelia (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Food diplomacy has increasingly attracted scholarly attention as a potent form of soft power used to shape national images and influence foreign publics. However, while much of the existing literature celebrates food diplomacy as an effective and benign instrument of cultural exchange, fewer studies critically interrogate its limitations, power dynamics, and long-term implications. This critical literature review evaluates key academic contributions by examining dominant theoretical perspectives, assessing empirical case studies, and identifying significant conceptual gaps. Moving beyond the standard narrative of